Relations Between the Development of Teaching and Theory of Mind in Early Childhood. Issue 2 (14th March 2016) - Ziv, Margalit; Solomon, Ayelet; Strauss, Sidney; Frye, Douglas
Abstract : The relations among children's theory of mind (ToM), their understanding of the intentionality of teaching, and their own peer teaching strategies were tested. Seventy-five 3-, 4-, and 5-year-olds completed 11 ToM and understanding-of-teaching tasks. Subsequently, 30 of the children were randomly chosen to teach a peer how to play a board game, and their teaching strategies and levels of contingent teaching were recorded. There were developmental changes in the children's understanding of teaching as an intentional activity. When teaching their peers, 3-year-olds used demonstration, whereas 4- and 5-year-olds added verbal explanations and began to adapt contingently to the learners' changing knowledge level. Relations among ToM, understanding of teaching, and teaching level were found. The results suggest that the development of children's teaching strategies and their contingency are closely tied to the development of ToM.